PELATIHAN PENGGUNAAN APLIKASI PENGGALANGAN DANA SECARA ONLINE PADA YAYASAN ASSALAFIYAH SURABAYA - Julianto Lemantara; Sulistiowati Sulistiowati; Hardman Budiardjo; Henry Bambang; A.B. Tjandrarini; Siswo Martono (Ekobis Abdimas, 2022)
Assalafiyah Foundation Surabaya is an orphanage foundation for orphans and the poor in Rungkut District, Surabaya City. Around 60% of the orphans fostered by this foundation come from outside Surabaya, so the payment of school fees is not from BOS funds. Therefore, the Assalafiyah foundation must find large enough funds to finance the schooling of these less fortunate children. In meeting school needs and other expenses, the foundation only receives regular monthly donors from the local community and not many non-permanent donors. With these limited funds, the Assalafiyah foundation must obtain funds from the wider community. Because the PkM implementing lecturer made a fundraising application for the Assalafiyah foundation. The problem is that the foundation does not yet know how to use the fundraising application, so the PkM implementing lecturers conduct training on the use of fundraising applications at the Assalafiyah foundation. The training materials include: maintenance of foundation activities, maintenance of donors, maintenance of foundation account data, maintenance of foster children's data, confirmation of donors, and donor history. Evaluation of the training by distributing questionnaires to 14 respondents from the Assalafiyah foundation. After being processed and analyzed, the results showed that the overall application was good.